The Fraunhofer Pattern of а Wave Field Generatingby a System оf Coherent Emitting Point Sources - Khachatrian, A. Zh.
The problem of description of a wave field generating by a system of coherent point sources is considered. This problem is discussed for two well-known approximations, the Fresnel and Fraunhofer patterns, correspondingly. It is shown, that for validity of the both approximations the problem has to contain two dimensionless small parameters. First of them is the wave parameter of the sources area and the second one is the wave parameter corresponding to the observation area. In the framework of the Fraunhofer pattern the Laue conditions of diffraction maximums for a system of periodic arranged sources is derived.
Keywords: Physics